2016
DOI: 10.2465/jmps.150722
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical characterization of radioactive particles from Fukushima soil using µ–XRD with synchrotron radiation

Abstract: Radioactive particles of around 50 µm size were collected from highly contaminated soil in the Fukushima Prefecture, Japan, and characterized using micro X-ray diffraction with synchrotron radiation (SR-µ-XRD). Two-dimensional diffraction patterns from individual particles rotated during X-ray irradiation were recorded on a flat imaging plate and a one-dimensional diffraction profile, as a function of 2θ, was derived from the pattern. Weathered biotite (WB) particles with plate-like morphology showed a broad p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The grain with the highest radioactivity reached 0.189 Bq, which is one order of magnitude higher than that of previously reported mineral grains. 16 The chemical composition of the two grains analyzed using EDS was consistent with that of biotite, but the K content was lower than expected for biotite, and Ca was present (Figure 2c). Hence, they were classified as WB, or biotite partially changed to vermiculite by weathering.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The grain with the highest radioactivity reached 0.189 Bq, which is one order of magnitude higher than that of previously reported mineral grains. 16 The chemical composition of the two grains analyzed using EDS was consistent with that of biotite, but the K content was lower than expected for biotite, and Ca was present (Figure 2c). Hence, they were classified as WB, or biotite partially changed to vermiculite by weathering.…”
supporting
confidence: 53%
“…14 In contrast, WB and other mineral grains of several dozen microns possess radioactivity on the order of 10 ¹2 Bq, at most. 16 Therefore, empirically there is a gap in radioactivity between CsMPs and mineral grains, such as WB. Using this gap, it was suggested that "hot spots" with more than 10 ¹2 Bq on an imaging plate (IP) are classified as CsMPs, 13,14 although distinction of CsMPs from radioactive mineral grains is not possible due to the low spatial resolution of IP.…”
mentioning
confidence: 99%
“…In our wet separation method, the separation of CsMP was always successful when the CsMPs contained more than 0.4 Bq 137 Cs. Motai et al (2016) separated soil particles containing 137 Cs from soils in Fukushima and measured the 137 Cs radioactivity in such soil particles. Their results showed that weathered biotite contains ~0.01 Bq 137 Cs and organic matter-bearing particles contain ~0.05 Bq 137 Cs.…”
Section: Methodsmentioning
confidence: 99%
“…(Mukai et al 2014) same. The radioactivity of each particle estimated from the intensity of the IP signal was in the range of 0.005 ~ 0.05 Bq (Motai et al 2016), which is far lower than that (a few Bq per particle) of radiocesium-bearing microparticles emitted directly from the broken pressure vessel of FDNPP (Adachi et al 2013;Yamaguchi et al 2016).…”
Section: Speciation Of the Radioactive Particles In The Soil Of Fukusmentioning
confidence: 90%
“…This paper reviews our recent research with respect to WB in Fukushima, including its structure and Cs-sorption/desorption properties, and discusses the role of WB in the radioactive contamination in Fukushima. Details of the experiments to obtain the results presented here are described in the original papers already published (Mukai et al 2014(Mukai et al , 2016aKikuchi et al 2015;Motai et al 2016).…”
Section: Introductionmentioning
confidence: 99%